Understanding Intergovernmental Relations: Key Features and Trends - Phillimore, John (Blackwell Publishing Asia P/L, 2013)
This article discusses several features of intergovernmental relations (IGR), paying particular attention to IGR in federations. A number of recent trends and challenges are identified, and implications are drawn for the analysis of IGR. The article shows how IGR has traditionally been dominated by informal processes and power relationships, but that formalisation and institutionalisation have increased and can provide greater certainty and protection for sub-national governments in dealing with central government.